(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2018)
The essay discusses about the overall results of the Lawfulness education’s history in the Italian school Research carried out by CROSS, Observatory on Organized Crime of Milan State University. It indicates the flow of a true pedagogical river that Italian society doesn’t see, but that has played an important role in the fight against Mafia phenomenon. The predominantly oral nature of the history reconstructed by the researchers, from the 1980s until todays, confirms this underestimation. This history moved through four evolutionary phases, from the pioneering to the one of the complete institutionalization and of the semantic consolidation. The different Italian regions have been participating in this movement elaborating their own action models, influenced by the contexts as well as by the main characters of collective and individual protagonists. This is, also, a history where people’s roles are central: teachers, students, public local administrators, witnesses. It is possible to draw the image of an original movement, plural but unified by strong common values, linked to lawfulness and justice ideas. Keywords: lawfulness education; school; teachers; antimafia; civil history; movement; models